PHYTOREMEDIATION OF SYNTHETIC WASTEWATER CONTAINING COPPER BY USING NATIVE PLANT - S.L.Zeki; M. J. M-Ridha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to assess the efficiency of N.oleander to remove heavy metals such as Copper (Cu) from wastewater. A toxicity test was conducted outdoor for 65-day to estimate the ability of N.oleander to tolerate Cu in synthetic wastewater. Based on a previous range-finding test, five concentrations were used in this test (0, 50, 100, 300, 510 mg/l). The results showed that maximum values of removal efficiency was found 99.9% on day-49 for the treatment 50 mg/l. Minimum removal efficiency was 94% day-65 for the treatment of 510 mg/l. Water concentration was within the permissible limits of river conservation and were 0.164 at day-35 for the 50 mg/l treatment, decreased thereafter until the end of the observation, and 0.12 at day-65 for the treatment 100 mg/l. the concentrations of water samples exceeded the permissible limits for 300 and 510 mg/l throughout the observation. Bioaccumulation factor (BAF) for N.oleaner was found to be greater than one for all the treatments. Higher translocation factor (TF) were 1.65, 1.73, 2.61 and 2.34 mg/l for 50, 100, 300 and 510 mg/l, respectively. This study revealed that N.oleander can tolerate and treat Cu concentration in wastewater.